The use of diplopods in soil ecotoxicology - A review - Souza, Tatiana da Silva; Christofoletti, Cintya Aparecida [UNESP]; Bozzatto, Vlamir [UNESP]; Fontanetti, Carmem Silvia [UNESP] (Elsevier B.V., 2014)
Diplopods play an important role in the dynamics of terrestrial ecosystems, actively participating in the decomposition of organic matter and soil aeration. They have gained increased attention from ecotoxicology research because they are continuously exposed to soil contaminants and biological effects of chemical stressors can be measurable at various levels of biological organization. This paper is the first review on the use of diplopods as soil bioindicators and compiles the effects of the different toxic chemical agents on these animals. Special emphasis is given on the interpretation of the effects of heavy metals and complex mixtures in target organs of diplopods. (C)2013 Elsevier Inc. All rights reserved.
Keywords: Millipedes; Terrestrial ecotoxicology; Soil toxicity; Biomarkers